Comparison of machining performance of microwave post-heated WC insert with dry, wet and MQL cutting in turning operation. Issue 2 (3rd April 2018) - Jhodkar, Durwesh; Chelladurai, H.; Choudhary, Akhilesh Kumar; Ramkumar, J.
ABSTRACT: This paper describes the application of microwave energy to enhance the machining performance of tungsten carbide tool insert in order to reduce the use of cutting fluids. Application of cutting fluids increases the machining costs, which include fluid consumption, maintenance and disposal costs. Health hazards for workers, environmental issues and economic aspects of cutting fluid motivate researchers to move towards coolant-free machining. This study aimed to minimize the dependency on cutting fluid during machining and to suggest a suitable alternative to improve the performance of tungsten carbide tool insert. Microwave post-treatment of tungsten carbide tool insert is the emerging technique in which the tool insert is subjected to microwave irradiation at a frequency of 2.5 GHz. In the present investigation, turning operations have been performed on AISI 1040 steel (American Iron and Steel Institue) using microwave-treated insert under dry cutting environment and untreated insert using dry, wet and minimum quantity lubrication (MQL) cutting environment. Variation of tool wear and surface roughness has been experimentally investigated in this study to evaluate the machining performance. Tool wear mechanism and chip morphology have been analysed using scan electron microscopy. The results indicate that microwave-treated insert achieved better performance than fresh tungsten carbide (WC/Co) inserts used in dry, wet and MQL cutting conditions.